Desenvolvimento de dispositivos descartáveis e de baixo custo para a detecção de biomarcadores relacionados ao câncer de colo uterino e endometrial - Baldo, Thaisa Aparecida (2019)
Cervical cancer (CC) and endometrial cancer (EC) are malignant neoplasms that affect women worldwide and the early diagnosis of these cancers is still limited. The incidence of these malignancies has been increasing year by year and, therefore, there is a great interest in new tools to enable a more accurate early diagnosis, increasing treatment efficiency and, consequently, reducing mortality rates. In this view, this work proposes the construction of disposable electrochemical devices for detection of CC and EC-related protein biomarkers by sandwich-type immunoassays using magnetic particles and nanoparticles for the capture and separation of analytes. These devices were manufactured using screen printing and inkjet printing techniques. The first work developed comprised the construction of screen-printing electrodes, composing a microfluidic cell that was constituted by an arrangement of 8 working electrodes connected with a pseudo-reference electrode and a counter electrode. The device was applied in the multiplexed detection of cyclooxygenase-2 (COX-2) and tumor protein Tp53 (Tp53) biomarkers. These devices were manufactured using screen printing and inkjet printing techniques. The first work developed comprised the construction of screen-printing electrodes, composing a microfluidic cell that was constituted by an arrangement of 8 working electrodes connected with a pseudo-reference electrode and a counter electrode. The device was applied in the multiplexed detection of cyclooxygenase-2 (COX-2) and tumor protein Tp53 (Tp53) biomarkers. For this, monoclonal antibodies (Ab1) were anchored on the surface of previously modified working electrodes with a bilayer formed poly (diallyldimethylammonium chloride) and gold nanoparticles (AuNPs) decorated with glutathione. Magnetic particles (PMs) modified with polyclonal antibodies (Ab2) and enzyme peroxidase (HRP) as electrochemical marker were used to capture and separate the biomarkers in serum samples from patients with CC and CE and injected into the microfluidic device for detection by immunoassay of the sandwich type. Low detection limits (LD) of 0.23 fg mL-1 and 0.18 fg mL-1 were obtained for COX-2 and Tp53, respectively. The second work consisted in the construction of a microfluidic device with 8 gold-based electrodes using an inkjet printer and applied in the detection of the biomarkers cyclin-dependent kinase inhibitor p16 (p16) and Tp53. This device comprised the use of self-assembled monolayers for anchoring the Ab1 and PMs decorated with Ab2 and HRP for capture and separation. The concentration range detected by this immunosensor was broad-ranging from pg to ng mL-1, with ultralow LD of 0.08 pg mL-1 for p16 and 0.04 pg mL-1 for Tp53. The third work consisted of the detection of the E6 oncoprotein associated with the human papillomavirus (HPV) using an electrochemical magneto-immunoassay. In this case, lipid-containing magnetic nanoparticles (LNPMs) were synthesized and modified with anti-E6 Ab1. After capture and separation of the biomarker, AuNPs decorated with Ab2 were added and the obtained immunoassay was captured on the surface of the electrode using a magnet positioned externally under the working electrodes. Detection of E6 was performed by the electrochemical gold response of AuNPs in hydrochloric acid by square wave voltammetry. The magnetic immunoassay presented a linear response for E6 between 4 pg mL-1 and 2.5 pg mL-1 with LD of 0.4 pg mL-1. The three immunoassays developed were applied in the detection of biomarkers in patient samples with CC and EC and presented excellent agreement when compared with the results obtained by enzyme-linked immunosorbent assay (ELISA). The methods proposed are promising tools for screening, early diagnosis, therapy management, and disease staging in clinical analyzes. of CC and EC, with advantages over the ELISA method, including speed, reproducibility, low cost, low detection limit, and low reagent and sample consumption.